Substance Use Disorder, Intravenous Injection, and HIV Infection: A Review. Issue 12 (December 2019) - Wang, Shao-Cheng; Maher, Brion
DSM-V-defined substance use disorder comprises four groups of symptoms: impaired control, social impairment, risky use, and pharmacological reactions. Behavioral patterns of impaired control, including impulsivity and risk taking, are associated with HIV risk behaviors. Substance users with stronger craving symptoms are more likely to use drugs via intravenous injection than other routes because of the faster drug effect and the higher bioavailability; thus, they are at high risk of HIV infection. HIV risk behaviors such as unprotected sex and intravenous injection facilitate HIV disease spread. Public health policies such as Needle and Syringe Exchange Programs and medication-assisted treatment are proven to reduce HIV risk behaviors such as the frequency of intravenous injection and even the incidence of HIV infection, but both of them have limitations. While intravenous injection is a frequently discussed issue in public policies and the HIV-related literature, it is a much less frequent topic in the addiction literature. We believed that understanding the mental substrate behind impulsivity/risk taking and the possible biological mechanism of intravenous injection may help in creating more effective strategies to slow down HIV infection.